2021
DOI: 10.3390/su13041920
|View full text |Cite
|
Sign up to set email alerts
|

Integrating a Local Asset/Resource into Tourism and Leisure Offering: The Case of Tea Resources in Longwu Town, Zhejiang Province, China

Abstract: The purpose of this article is to report on a research project in the field of tea tourism. The project’s aim was to identify the prerequisites and critical success factors for and to suggest the adequate strategies to achieve an effective pairing/partnership between the tea industry and tourism/leisure activities. Drawing on the blended theoretical foundations of sustainable tourism development, community-based tourism, and strategic marketing planning, this study first analyzed the tea offering as a tourism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…Tea culture tourism is an aspect of cultural tourism that also includes activities like doing business, getting an education, and harvesting own tea. Based on these definitions, it seems more appropriate to describe tea tourism as "tea-driven" or "tea-related tourism" (Yan et al, 2021). This findings concur with Guo et al (2019) that how the tea industry benefits the surrounding agricultural, industrial, and service sectors while additionally working as an important tourist attraction.…”
Section: Strategic Marketing Planningsupporting
confidence: 55%
“…Tea culture tourism is an aspect of cultural tourism that also includes activities like doing business, getting an education, and harvesting own tea. Based on these definitions, it seems more appropriate to describe tea tourism as "tea-driven" or "tea-related tourism" (Yan et al, 2021). This findings concur with Guo et al (2019) that how the tea industry benefits the surrounding agricultural, industrial, and service sectors while additionally working as an important tourist attraction.…”
Section: Strategic Marketing Planningsupporting
confidence: 55%
“…Scholarly literature on tea tourism is mainly concentrated on the supply side (tea plantations), with limited attention given to demand perspectives (tourists) [33]. Supplyside research mostly uses qualitative and stakeholder approaches [8], with attention given to tea tourism development [34,35], community livelihood and well-being [36], labor division [37], integration of tea plantation and tea tourism [38], and ecological systems [39]. Demand-oriented research is primarily quantitative.…”
Section: Tea Tourismmentioning
confidence: 99%
“…The promotion and cultivation of tea may contribute to the preservation of cultural heritage and customs, as well as offer economic prospects for rural communities (Ng et al, 2022)(Bulut Solak & Amin, 2020). It has been observed that proper planning and development of tea tourism can effectively help generate additional revenue and boost the rural economy (Yan et al, 2021). Thus, it is imperative to manage the integration of tea offering and tourism/leisure activities effectively to ensure the sustainable operation of tea tourism (Sanjiv Kumar Sharma et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%